A ternary lithium ion battery nonaqueous electrolyte and a ternary lithium ion battery thereof
Patent Information
- Application Number
- CN202611125004.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-23
AI Technical Summary
然而,随着市场对电池能量密度和快充性能要求的不断提高,三元材料,尤其是高镍三元材料,在应用中也暴露出一些固有的问题
[0026]为更好地说明本发明的目的、技术方案和有益效果,下面将结合具体实施例对本发明作进一步说明。需说明的是,下述实施所述方法是对本发明做的进一步解释说明,不应当作为对本发明的限制。
Smart Images

Figure CN122968443A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a non-aqueous electrolyte for ternary lithium-ion batteries and the ternary lithium-ion battery thereof. Background Technology
[0002] Ternary lithium-ion batteries (using lithium nickel cobalt manganese oxide (NCM) or lithium nickel cobalt aluminum oxide (NCA) as cathode materials) have become one of the preferred power sources for electric vehicles and large-scale energy storage systems due to their advantages such as high energy density, high output voltage, and long cycle life. However, with the increasing market demands for battery energy density and fast-charging performance, ternary materials, especially high-nickel ternary materials, have also revealed some inherent problems in applications. First, the high oxidizability of ternary materials, particularly in their delithiated state, can catalyze the violent oxidative decomposition of conventional organic electrolytes (such as carbonates) on the electrode surface, leading to increased battery impedance, accelerated capacity decay, and gas generation, causing battery swelling. Second, under abusive conditions such as high temperature or overcharging, the structural stability of ternary materials is poor, resulting in a violent exothermic reaction with the electrolyte and a significant risk of thermal runaway, seriously threatening battery safety. In addition, the instability of the solid-liquid interface (SEI film) of the graphite anode at high temperatures, high rates, or during cycling can also consume active lithium, further restricting the overall performance and lifespan of the battery. Therefore, developing a highly stable and safe electrolyte system that matches the highly active ternary cathode and graphite anode has become a key technological bottleneck in promoting the development of high-energy-density lithium-ion batteries. Summary of the Invention
[0003] In view of the above problems, the purpose of this invention is to provide a non-aqueous electrolyte for ternary lithium-ion batteries and a ternary lithium-ion battery thereof. The non-aqueous electrolyte contains a first additive and a second additive with a special structure. Through the synergistic effect of the two, impedance can be effectively reduced and the fast charging cycle performance of the ternary lithium-ion battery under high voltage can be improved.
[0004] To achieve the above objectives, the present invention provides a non-aqueous electrolyte for ternary lithium-ion batteries, comprising a lithium salt, a non-aqueous organic solvent, and additives, wherein the additives include a first additive shown in structural formula one.
[0005] Structural Formula 1 And, the second additive shown in structural formula two,
[0006] Structural Form 2 R1 and R2 are each independently selected from C1 to C6 alkyl groups, or R1 and R2 are combined to form a cyclic structure. R1 and R2 are each independently selected from hydrogen or C1 to C6 alkyl groups. n is selected from 0 or 1, and m is selected from 0 or 1.
[0007] Compared with the prior art, the non-aqueous electrolyte of the present invention contains a first additive shown in structural formula one and a second additive shown in structural formula two. The first additive is a phosphorus oxide compound containing isocyanate groups, which preferentially oxidizes at high voltage on the positive electrode surface and achieves chemical anchoring through its highly reactive groups, decomposing to generate a robust CEI film rich in highly ion-conductive Li3PO4 and other components. This film not only inhibits electrolyte oxidation and positive electrode structural degradation but also reduces the generation of acidic byproducts at the source, directly lowering the positive electrode charge transfer impedance. Meanwhile, the sulfate ester compound shown in structural formula two is preferentially reduced at the negative electrode, forming a flexible organic sulfide and highly ion-conductive Li2S and Li... x SO y The stable SEI film, characterized by its excellent elasticity and lithium-ion conductivity, ensures rapid and uniform lithium-ion insertion during fast charging. Together, these two components contribute to a high-mechanical-strength interface film on both the positive and negative electrodes, suppressing lithium dendrite growth and thus promoting the fast-charge cycle performance of ternary lithium-ion batteries.
[0008] Preferably, R1 and R2 are each independently selected from C1 to C3 alkyl groups, or R1 and R2 are combined to form a cyclic structure, R1 and R2 are each independently selected from hydrogen or C1 to C3 alkyl groups, n is selected from 0 or 1, and m is selected from 0 or 1.
[0009] Preferably, the first additive includes at least one of compounds 1 to 4.
[0010] Compound 1, Compound 2, Compound 3, Compound 4.
[0011] Among them, the CAS number of compound 1 is 17419-12-4; the CAS number of compound 2 is 31334-44-8; the CAS number of compound 3 is 20039-33-2; and the CAS number of compound 4 is 17419-15-7.
[0012] Preferably, the second additive includes at least one of compounds 5 to 7.
[0013] Compound 5, Compound 6, Compound 7.
[0014] Among them, compound 5 has the CAS number 1072-53-3; compound 6 has the CAS number 3741-38-6; and compound 7 has the CAS number 40811-14-1.
[0015] Preferably, the first additive of the present invention accounts for 0.05% to 5.0% of the total mass of the lithium salt, non-aqueous organic solvent, and additive. More preferably, the first additive accounts for 0.1% to 4% of the total mass of the lithium salt, non-aqueous organic solvent, and additive. More preferably, the first additive accounts for 0.5% to 2.5% of the total mass of the lithium salt, non-aqueous organic solvent, and additive. As examples, the first additive accounts for 0.05%, 0.08%, 0.1%, 0.2%, 0.4%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, and 5.0% of the total mass of the lithium salt, non-aqueous organic solvent, and additive, but is not limited thereto, and other unlisted values within the scope of the present invention are also applicable.
[0016] Preferably, the second additive of the present invention accounts for 0.05% to 5.0% of the total mass of the lithium salt, non-aqueous organic solvent, and additive. More preferably, the second additive accounts for 0.5% to 3.0% of the total mass of the lithium salt, non-aqueous organic solvent, and additive. More preferably, the second additive accounts for 0.8% to 2.0% of the total mass of the lithium salt, non-aqueous organic solvent, and additive. As examples, the second additive accounts for 0.05%, 0.08%, 0.1%, 0.2%, 0.4%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, and 5.0% of the total mass of the lithium salt, non-aqueous organic solvent, and additive, but is not limited thereto, and other unlisted values within the scope of the present invention are also applicable.
[0017] Preferably, the lithium salt of the present invention is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalateborate)borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium fluorosulfonate (LiSO2F), lithium difluorooxalateborate (LiODFB), lower aliphatic carboxylic acids, lithium difluorodioxalate phosphate (LiDFOP), and lithium bis(fluorosulfonyl)imide (LiFSI).
[0018] Preferably, the lithium salt of the present invention accounts for 8-30% of the total mass of the lithium salt, non-aqueous organic solvent, and additives. Further, the lithium salt accounts for 10-25% of the total mass of the lithium salt, non-aqueous organic solvent, and additives. More preferably, the lithium salt accounts for 10-15% of the total mass of the lithium salt, non-aqueous organic solvent, and additives. As examples, the lithium salt accounts for 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 24%, 25%, 26%, 28%, and 30% of the total mass of the lithium salt, non-aqueous organic solvent, and additives. However, this is not a limitation, and other values not listed within the scope of the present invention are also applicable.
[0019] Preferably, the non-aqueous organic solvent is selected from at least one of carbonate solvents, carboxylic acid ester solvents, and ether solvents. Specifically, carbonate solvents may be selected from ethylene carbonate (EC), propylene carbonate, butyl carbonate (BC), amyl carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), methyl n-propyl carbonate, ethyl n-propyl carbonate, and propylene carbonate (PC); carboxylic acid ester solvents may be selected from γ-butyrolactone, γ-valerolactone, δ-valerolactone, methyl acetate (MA), ethyl acetate (EA), ethyl propionate (EP), butyl acetate (n-Ba), and acetic acid esters. Propyl propionate (n-PP) and butyl propionate; the ether solvent may be selected from at least one of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether may specifically include, but is not limited to, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether.
[0020] Preferably, the non-aqueous organic solvent accounts for 60% to 90% of the total mass of the lithium salt, the non-aqueous organic solvent, and the additive. More preferably, the non-aqueous organic solvent accounts for 72% to 89% of the total mass of the lithium salt, the non-aqueous organic solvent, and the additive. More preferably, the non-aqueous organic solvent accounts for 75% to 88% of the total mass of the lithium salt, the non-aqueous organic solvent, and the additive. As examples, the non-aqueous organic solvent accounts for 60%, 65%, 70%, 72%, 74%, 75%, 78%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, and 90% of the total mass of the lithium salt, the non-aqueous organic solvent, and the additive. However, this is not a limitation, and other values not listed within the scope of this invention are also applicable.
[0021] Preferably, the additive of the present invention further includes an auxiliary agent selected from at least one of vinylene carbonate (VC), vinylene carbonate (VEC), fluorovinyl carbonate (FEC), vinyl sulfite (ES), 1,3-propanesulfonate lactone (PS), 1,3-propenesulfonate lactone (PST), 1,4-butanesulfonate lactone (1,4-BS), vinyl sulfate (DTD), succinic anhydride (SA), and maleic anhydride (MA). Preferably, the auxiliary agent of the present invention is selected from vinylene carbonate (VC). Further, the auxiliary agent accounts for 0.1% to 8% of the total mass of the lithium salt, non-aqueous organic solvent, and additive. For example, the auxiliary agent accounts for 0.1%, 0.5%, 0.8%, 1.0%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, and 8% of the total mass of the lithium salt, non-aqueous organic solvent, and additive.
[0022] Another aspect of the present invention provides a ternary lithium-ion battery, comprising a positive electrode active material, a negative electrode active material, and an electrolyte, wherein the electrolyte is the aforementioned non-aqueous electrolyte for ternary lithium-ion batteries.
[0023] Preferably, the maximum charging voltage of the ternary lithium-ion battery of the present invention is 4.45V.
[0024] Preferably, the positive electrode active material of the present invention is selected from nickel cobalt manganese oxide or nickel cobalt aluminum oxide, and the nickel content is not less than 60%. Specifically, the chemical formula of the nickel cobalt manganese oxide is LiNi. x Co y Mn z M (1-x-y-z) O2, the chemical formula of nickel cobalt aluminum oxide is LiNi x Co y Al z N (1-x-y-z) O2, wherein M is at least one of Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, and Ti, N is at least one of Mn, Mg, Cu, Zn, Sn, B, Ga, Cr, Sr, V, and Ti, 0.6 ≤ x < 1, 0 <y<0.4,0<z<0.4,x+y+z≤1。
[0025] Preferably, the negative electrode active material of the present invention is selected from at least one of artificial graphite, natural graphite, lithium titanate, silicon-carbon composite material, and silicon suboxide. More preferably, the negative electrode active material of the present invention is selected from artificial graphite or natural graphite. Detailed Implementation
[0026] To better illustrate the purpose, technical solution, and beneficial effects of this invention, the invention will be further described below with reference to specific embodiments. It should be noted that the methods described below are further explanations of this invention and should not be construed as limiting it.
[0027] Example 1 (1) Preparation of non-aqueous electrolyte In an argon atmosphere and a vacuum glove box with a moisture content of <1ppm, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a weight ratio of EC:EMC=3:7 to obtain 86.8g of non-aqueous organic solvent. Then, 0.2g of compound 1 and 0.5g of compound 5 were added, dissolved, and stirred thoroughly. After that, 12.5g of lithium hexafluorophosphate (LiPF6) was added and mixed evenly to obtain a non-aqueous electrolyte.
[0028] (2) Preparation of positive electrode Nickel cobalt manganese oxide LiNi 0.6 Co 0.2 Mn 0.2 The binder PVDF and the conductive agent SuperP are mixed evenly at a mass ratio of 96:2.5:1.5 to prepare a positive electrode slurry of a certain viscosity. The mixed slurry is coated on both sides of aluminum foil, dried, and rolled to obtain the positive electrode sheet.
[0029] (3) Preparation of negative electrode A negative electrode slurry of a certain viscosity is prepared by mixing artificial graphite, PVDF binder and SuperP conductive agent at a mass ratio of 90:2:8. The slurry is then coated on both sides of a copper foil, dried and rolled to obtain a negative electrode sheet.
[0030] (4) Preparation of ternary lithium-ion batteries The positive electrode, separator, and negative electrode are stacked in sequence, and then layered as needed. After the tabs are welded, they are placed in the aluminum-plastic film of the battery packaging. The prepared non-aqueous electrolyte is injected into the dried bare cell. Vacuum sealing, settling, formation (0.05C constant current charging to 3.9V, then 0.1C constant current charging to 4.45V), shaping, and capacity testing are performed sequentially to obtain a 1Ah soft-pack ternary lithium-ion battery.
[0031] The formulations of the non-aqueous electrolytes for ternary lithium-ion batteries in Examples 1-12 and Comparative Examples 1-6 are shown in Table 1. The electrolyte preparation, positive electrode preparation, negative electrode preparation, and preparation of ternary lithium-ion batteries in Examples 2-12 and Comparative Examples 1-6 are the same as in Example 1.
[0032] Table 1. Non-aqueous electrolyte formulations for examples and comparative examples.
[0033] The structure of compound A is shown in Table 1.
[0034] Compound A The lithium-ion batteries prepared in Examples 1-12 and Comparative Examples 1-6 were subjected to fast charge cycle tests and electrochemical impedance spectroscopy tests, respectively. The specific test conditions are as follows, and the performance test results are shown in Table 2.
[0035] Lithium-ion battery fast charging cycle performance test The lithium-ion battery was placed in a 25°C constant temperature chamber and left to stand for 30 minutes to reach a constant temperature. It was then charged at a constant current of 4C until the voltage reached 4.45V, followed by constant voltage charging at 4.45V until the current reached 0.05C. Next, it was discharged at a constant current of 4C until the voltage reached 3.0V. The first discharge capacity was recorded as C0, constituting one charge-discharge cycle. Then, 800 cycles of 4C / 4C charge and discharge were performed at 25°C, with the discharge capacity recorded as C1. The capacity retention rate of the lithium-ion battery was calculated using the following formula.
[0036] Capacity retention rate = (C1 / C0) × 100% Electrochemical AC impedance performance testing of lithium-ion batteries The lithium-ion battery was placed in a 25°C constant temperature chamber and left to stand for 30 minutes to reach a constant temperature. It was then charged at a constant current of 0.33 C until the voltage reached 4.45V, followed by a constant voltage charge of 4.4V until the current reached 0.05C. Next, it was discharged at a constant current of 0.33C until the voltage reached 3.0V. The first discharge capacity was recorded as 100% SOC. The battery was then charged again at a constant current of 0.33C until the voltage reached 4.45V, followed by a constant voltage charge of 4.45V until the current reached 0.05C. Finally, it was discharged at a constant current of 0.33C until 50% SOC was reached. The electrochemical impedance spectroscopy (EIS) was measured using an electrochemical workstation with an open-circuit voltage, an amplitude of 10 mV, and a frequency range of 0.01Hz to 1000000Hz.
[0037] Table 2 Performance test results of the examples and comparative examples
[0038] As shown in Table 1, compared to Comparative Examples 1-6, Examples 1-12 of the present invention exhibit superior fast-charging cycle performance and lower impedance at a high voltage of 4.45V. This may be because the non-aqueous electrolyte of the present invention contains a first additive shown in structural formula 1 and a second additive shown in structural formula 2. The first additive is a phosphorus oxide compound containing isocyanate groups, which preferentially oxidizes on the positive electrode surface under high voltage and achieves chemical anchoring through highly reactive groups, decomposing to generate a robust CEI film rich in high-ionic-conductivity Li3PO4 and other components. This film not only inhibits electrolyte oxidation and positive electrode structure degradation but also reduces the generation of acidic byproducts from the source, directly lowering the positive electrode charge transfer impedance. Meanwhile, the sulfate ester compound shown in structural formula 2 is preferentially reduced at the negative electrode, forming flexible organic sulfides and high-ionic-conductivity Li2S and Li x SO y The stable SEI film, characterized by its excellent elasticity and lithium-ion conductivity, ensures rapid and uniform lithium-ion insertion during fast charging. Together, these two components contribute to a high-mechanical-strength interface film on both the positive and negative electrodes, suppressing lithium dendrite growth and thus promoting the fast-charge cycle performance of ternary lithium-ion batteries.
[0039] As shown in Examples 7-10, when the first additive is Compound 1, its fast-charge cycle performance at a high voltage of 4.45V is superior, and its impedance is lower. This may be because the five-membered cyclic phosphorus heterocycle reduces the Li + Desolvation energy and fast charging kinetics are improved. As can be seen from Examples 7 and 11-12, when the second additive is compound 5, its performance is better. This may be because compound 5 and compound 1 can synergistically construct a sulfur-rich SEI with better ionic conductivity and high mechanical stability on the negative electrode side, thereby reducing impedance.
[0040] As can be seen from Comparative Examples 2 to 5, the absence of either the first additive or the second additive will lead to a deterioration in its fast charging cycle performance at a high voltage of 4.45V and an increase in impedance. This indicates that only when the two are used together can a better performance improvement be achieved.
[0041] As shown in Comparative Example 6, when the first additive is replaced with compound A, the fast charging cycle performance at a high voltage of 4.45V is significantly reduced because compound A does not contain isocyanate groups.
[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A non-aqueous electrolyte for a ternary lithium-ion battery, comprising a lithium salt, a non-aqueous organic solvent, and additives, characterized in that, The additive includes a first additive shown in structural formula one. Structural Formula 1 And, the second additive shown in structural formula two, Structural Form 2 R1 and R2 are each independently selected from C1 to C6 alkyl groups, or R1 and R2 are combined to form a cyclic structure. R1 and R2 are each independently selected from hydrogen or C1 to C6 alkyl groups. n is selected from 0 or 1, and m is selected from 0 or 1.
2. The non-aqueous electrolyte for ternary lithium-ion batteries according to claim 1, characterized in that, R1 and R2 are each independently selected from C1 to C3 alkyl groups, or R1 and R2 are combined to form a cyclic structure. R1 and R2 are each independently selected from hydrogen or C1 to C3 alkyl groups. n is selected from 0 or 1, and m is selected from 0 or 1.
3. The non-aqueous electrolyte for ternary lithium-ion batteries according to claim 1, characterized in that, The first additive includes at least one of compound 1 to compound 4. Compound 1, Compound 2, Compound 3, Compound 4.
4. The non-aqueous electrolyte for ternary lithium-ion batteries according to claim 1, characterized in that, The second additive includes at least one of compounds 5 to 7. Compound 5, Compound 6, Compound 7.
5. The non-aqueous electrolyte for ternary lithium-ion batteries according to claim 1, characterized in that, The first additive accounts for 0.05% to 5% of the total mass of the lithium salt, the non-aqueous organic solvent, and the additive, and the second additive accounts for 0.05% to 5% of the total mass of the lithium salt, the non-aqueous organic solvent, and the additive.
6. The non-aqueous electrolyte for ternary lithium-ion batteries according to claim 1, characterized in that, The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalate-borate), lithium difluorophosphate, lithium fluorosulfonate, lithium difluorooxalate-borate, lithium lower aliphatic carboxylic acids, lithium difluorodioxalate phosphate, and lithium bis(oxalate-imide).
7. The non-aqueous electrolyte for ternary lithium-ion batteries according to claim 1, characterized in that, The non-aqueous organic solvent is selected from at least one of carbonate solvents, carboxylic acid ester solvents, and ether solvents.
8. A ternary lithium-ion battery, comprising a positive electrode active material, a negative electrode active material, and an electrolyte, characterized in that, The electrolyte is the non-aqueous electrolyte for ternary lithium-ion batteries as described in any one of claims 1 to 7.
9. The ternary lithium-ion battery according to claim 8, characterized in that, The maximum charging voltage is 4.45V.
10. The ternary lithium-ion battery according to claim 8, characterized in that, The positive electrode active material is selected from nickel cobalt manganese oxide or nickel cobalt aluminum oxide, and the nickel content is not less than 60%.
